2021
DOI: 10.3390/molecules26082350
|View full text |Cite
|
Sign up to set email alerts
|

Micro Salting-Out Assisted Matrix Solid-Phase Dispersion: A Simple and Fast Sample Preparation Method for the Analysis of Bisphenol Contaminants in Bee Pollen

Abstract: In the present work, a novel sample preparation method, micro salting-out assisted matrix solid-phase dispersion (μ-SOA-MSPD), was developed for the determination of bisphenol A (BPA) and bisphenol B (BPB) contaminants in bee pollen. The proposed method was designed to combine two classical sample preparation methodologies, matrix solid-phase dispersion (MSPD) and homogenous liquid-liquid extraction (HLLE), to simplify and speed-up the preparation process. Parameters of μ-SOA-MSPD were systematically investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…3 A Main purpose of the analyzed studies as revealed by the publications in Table S1. B Overlapped main purposes with other secondary objectives of the analyzed papers [64] or by air pollution near polycarbonate molding plants [65], bee pollen [66], mussels [67] and brine shrimp [68]. Food contamination was determined in meat samples [53], beverages [55,69,70], milk [59,63,71,72], oils [56,63], and canned food products [59,71,73] with most studies revealing that BPA could be leached from the plastic can linings, packaging, and bottles [53,55,56,71,[74][75][76].…”
Section: Temporal Distribution and Purpose Of The Selected Articlesmentioning
confidence: 99%
“…3 A Main purpose of the analyzed studies as revealed by the publications in Table S1. B Overlapped main purposes with other secondary objectives of the analyzed papers [64] or by air pollution near polycarbonate molding plants [65], bee pollen [66], mussels [67] and brine shrimp [68]. Food contamination was determined in meat samples [53], beverages [55,69,70], milk [59,63,71,72], oils [56,63], and canned food products [59,71,73] with most studies revealing that BPA could be leached from the plastic can linings, packaging, and bottles [53,55,56,71,[74][75][76].…”
Section: Temporal Distribution and Purpose Of The Selected Articlesmentioning
confidence: 99%
“…Matrix solid phase dispersion (MSPD) was first introduced by Barker in 1989 as a novel sample preparation method, with many advantages such as reducing sample and reagent consumption and lower costs (Barker, 2000). Recently, an increasing number of modified MSPD extraction methods have been established by researchers, including ultrasound-assisted MSPD (UA-MSPD) (Dos Santos et al, 2019), vortex-assisted MSPD (VA-MSPD) (de Melo Malinowski et al, 2022), and micro salting-out assisted MSPD (µ-SOA-MSPD) (Zhang et al, 2021), which simplify the extraction procedures of traditional MSPD and reduce both the loss of target components and the sample pretreatment time. Currently, these modified MSPD methods have been used for the extraction of active components from various herbs medicines such as terpenoids, flavonoids, and alkaloids (Wang et al, 2019;Chen et al, 2021;Zheng et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…10 Homogeneous liquid–liquid extraction (HLLE) is regarded as a viable alternative to conventional extraction techniques. 11 The HLLE technique has two steps: initially, an aqueous sample solution containing analytes is combined with an extractant to form a homogeneous phase; subsequently, the separation of organic phases is achieved through the addition of reagents such as salt, 12 sugar, 13 hydrophobic solvents, 14 or other substances, resulting in a change in the layered or de-emulsified composition. Compared with traditional liquid–liquid extraction techniques, HLLE has the advantages of high efficiency, time-saving, low-cost, and eco-friendliness.…”
Section: Introductionmentioning
confidence: 99%